The Diagnosis of Vertebrobasilar Insufficiency Using Transcranial Doppler Ultrasound. (8th November 2012) - Alnaami, Ibrahim; Siddiqui, Muzaffer; Saqqur, Maher
Abstract : Background . Vertebrobasilar insufficiency (VBI) is a hemodynamic posterior circulation transient ischemic attack (TIA) caused by intermittent vertebral artery occlusion that is induced by a head rotation or extension. VBI may result from large vessel atherosclerotic disease, dissection, cervical compressive lesions, and subclavian steal phenomenon. Diagnostic transcranial Doppler (TCD) of VBI disease and hemodynamic posterior circulation TCD monitoring in symptomatic positions might prove a useful tool in establishing the diagnosis. Patient and Material/Method . A 50-year-old Caucasian man presented with a one-year history of episodic positional vertigo and ataxic gait that were induced by a neck extension and resolved by an upright position or a neck flexion. Computed tomography angiogram (CTA) and TCD confirmed the presence of VBI where no blood flow was detected through posterior cerebral arteries in the symptomatic position (head extension position). Conclusion . TCD is a promising noninvasive technique that might have a role as a diagnostic test in VBI.